Comparison of activity-based costing and time-driven activity-based costing for printed circuit board assembly production - Nur Syafikah, Pinueh; Mohd Yazid, Abu; Nurul Haziyani, Aris; Muhammad Arieffuddin, Mohd Jamil; Emelia Sari, . (JATIT, 2024)
The number of resources employed determines product costs in traditional costing analysis (TCA). TCA is flawed because manufacturing overhead may be substantially larger than the basis of allocation, therefore a little change in resource volume causes a big change in overhead. Thus, activity-based costing (ABC) was created to solve TCA’s cost allocation issues by analyzing overhead expenses and cost drivers more thoroughly. Many cost factors may be utilized to identify overhead causes and reduce overhead expenses. ABC was theoretically inappropriate to overlook spare capacity that may help forecasting. For that reason, time-driven activity-based costing (TDABC) has been studied because it maximizes capacity cost rate and time equations to create underused capacity information. This purpose of this study observes, analyses, and compares ABC and TDABC methods to determine which is more effective for production. Four steps comprise this study’s approach. Phase 1 defines the problem, while phase 2 involves data collecting on location. Phase 3 implements ABC and TDABC methodologies and compares their costing analyses. The last phase, phase 4 concludes this research. As a result, this study shows ABC is transparent and can forecast unit product cost using cost driver rate. TDABC has objective cost driver determination, eliminates time-consuming processes, various cost drivers, and capacity utilization analysis for forecasting and planning. Thus, the comparative study met the third purpose of comparing ABC and TDABC costs sustainment utilizing numerous aspects. Finally, TDABC is the best practice because it provides better information than ABC in cost allocation, driver determination, action taken for an additional activity, cost consideration, informative, transparency, oversimplification of activities, and capacity forecast.